Social support and mental health in late adolescence are correlated for genetic, as well as environmental, reasons. Issue 1 (December 2017) - Wang, R.; Davis, Oliver; Wootton, Robyn; Mottershaw, Abigail; Haworth, Claire
Abstract Late adolescence is a crucial, but underexplored, developmental stage with respect to the aetiology of social support. These individuals are experiencing many major life changes and social support can help them adjust to the associated environmental stressors of this time. Using 1, 215 18-year-old twin pairs from the Twins Early Development Study, we collected measures of two indices of support: support quality and support quantity, as well as wellbeing and depression. Both support indices were moderately heritable (55% and 49%, respectively), an interesting finding given the many environmental changes that late adolescents are encountering that could be environmentally altering their social network structures. Finding a genetic influence on support suggests the presence of gene-environment correlation whereby individuals create and perceive their supportive environment based upon their genetic predispositions. Shared genetic influences mediated the moderate phenotypic correlation (mean r = 0.46) between support and mental health. Genetic correlations were higher between support quality and mental health (mean rA = 0.75), than between support quantity and mental health (mean rA = 0.54), reflecting the phenotypic pattern. This suggests that interventions should focus more on making late adolescents aware of the support quality around them than encouraging them to increase their social network size.